Pengaruh Metode Pembelajaran Dan Latar Belakang Pendidikan Orang Tua Siswa Terhadap Kemampuan Berbicara Bahasa Inggris (Eksperimen pada Madrasah Aliyah Swasta di Kabupaten Indramayu) - Budi Satrio (Universitas Persada Indonesia YAI, 2020)
This research is a kind of quasi-experimental research which aims to know the effectof Learning Method and Parent’s Education Background on English Speaking Ability.This research uses post test only for control group design. The population of this study isall student of class X private Madrasah Aliyah in Kabupaten Indramayu term 2018/2019in even semester taken with purposive sampling technique that takes two classes from theexisting population to be used as a sample. Research data is in a quantitative data formatwhich is reflected by the result of post test score of English speaking ability. Based on thehypothesis test, we got the results as follow: (1), There is a significant effect of learningmethod on student’s English speaking ability in private Madrasah Aliyah in KabupatenIndramayu. It is proved by Sig.value = 0.005 < 0.05 and F count = 8.236; (2) There is asignificant effect of Parent’s Education Background on student’s English speakingability. It is proved by Sig.value = 0.039 < 0.05 and F count = 4.398; (3) There is asignificant interactive effect of learning method and Parent’s Education Background onstudent’s English speaking ability in private Madrasah Aliyah in Kabupaten Indramayu. Itis proved by Sig.value 0.023 < 0.05 and F count = 5.373